ON GENERATING CULTURALLY SUSTAINABLE ENTERPRISES AND DEMAND-RESPONSIVE SERVICES IN REMOTE ABORIGINAL SETTINGS: A CASE STUDY FROM NORTH-WEST QUEENSLAND - Paul Memmott (Journal of Architecture&ENVIRONMENT, 2012)
The catalyst for this paper was the continuation of poor national outcomes in Aboriginal employment and quality of lifestyle, despite 35 years of sustained gover-nment service delivery. The persistence of Aboriginal identities and cultures, albeit in transformed states, is a dominant continuity despite the pulses and shifts of policies. Nevertheless, debate has recently embraced whether Aboriginal people can participate in the market economy and yet still retain traditional culture (Sarra 2009), and whether retention of traditional culture has contributed inadvertently to community dysfunction (Altman 2009;Sutton 2009). The paper explores a case study of remote Aboriginal cultural and socioeconomic empowerment situated within the fields of both mainstream economy and service delivery in the Myuma Group. From the research, there is a range of significant good-practice strategies and methods underpinning Myuma’s success. In historical order, the first was the use of a native title claim from which to obtain an initial set of economic assets (infra structure, contracts). A second strategy was an inclusive (rather than exclusive) approach to spreading the enterprise benefits created by a small Indjilandji extended family group to a regional bloc of multiple language groups and to other beneficiaries in the wider community. This enabled the Myuma Group to project itself as a benefactor for the regional Aboriginal population (not simply as a nepotistic family-based firm) an image that was essential to attract strong government support and local and regional legitimacy.